Depressive Behavior and Coronary Artery Atherogenesis in Adult Female Cynomolgus Monkeys - Shively, Carol A. (2008)
OBJECTIVE: To examine depressive behavior and early coronary artery atherogenesis in 36 socially housed female cynomolgus monkeys, an established model of atherogenesis and depression. Coronary heart disease (CHD) is caused by coronary artery atherosclerosis (CAA) and its sequelae which develop over a period of decades. Thus, in prospective studies of depression and CHD, CAA was likely present at baseline in most subjects who experienced cardiac events. Little is known about the relationship between depression and CAA. METHODS: The monkeys were free of atherosclerosis before being fed a diet containing moderate amounts of fat and cholesterol for 52 months. Depressed behavior and activity levels recorded in weekly 15-minute focal samples, telemetered 24-hour heart rate, plasma total (TPC) and high-density lipoprotein cholesterol (HDLC), luteal phase serum progesterone concentrations, basal cortisol, cortisol response to corticotrophin-releasing hormone (CRH), and CAA extent were assessed. RESULTS: Time spent in depressed behavior over 4 years was significantly associated with early CAA (r = 73, p = .001), as were activity level, 24-hour heart rate, TPC, HDLC, cortisol response to CRH, and mean peak progesterone (all p ≤ 0.05). Depressed females had four times the CAA compared with nondepressed females. CONCLUSIONS: Depression in primates is associated with perturbations in multiple CHD risk factors and accelerated early atherogenesis. These data are consistent with the hypotheses that depression and CAA both stem from a common mechanism and that depression may cause CAA.